COMPUTER SYSTEMS OF DIGITALIZATION OF PRODUCTION AND BUSINESS PROCESSES IN THE AGRO-INDUSTRIAL COMPLEX - CHUIENKO, VITALII; TAZETDINOV, VALERII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article is devoted to the study of computer systems for digitalization of production and business processes in the agro-industrial complex, in particular, dairy farming. The agro-industrial complex includes a set of industries that provide food to the country's population. Food security is currently one of the top priorities on a global scale. In order to realize this direction, the main task of the agro-industrial complex is to reduce the costs of production and processing of products and to improve the working conditions of employees. The object of the article is the formation of systems for digitalization of production and business processes, and the main directions of its implementation in the activities of an enterprise. The structure of the agro-industrial complex and the general scheme of digitalization of business processes of an agro-industrial enterprise are determined. The constant development of society requires constant changes in the formation of business processes. The paper presents schemes of digitalization systems for the business processes of the agro-industrial complex by the directions of their implementation. The article considers one of the most labor-intensive branches of agriculture that forms the agro-industrial complex, namely livestock, in particular dairy farming. Its development depends on material and technical support and production processes. The author considers a number of technological operations and the possibility of their digitalization in order to form a system of digitalization of the business process of milk production. Thanks to the digitalization of business processes, the company has quick access to databases on the availability and use of resources and facilitates effective decision-making to improve production efficiency and product competitiveness. The creation of computerized digitalization systems makes it possible to promptly display each production process, improves access to information, its quality and speed of perception. Accordingly, it helps to simplify the accounting process, improve the competitiveness of the enterprise, optimize labor resources, which accompanies cost reduction and increase in labor productivity, and saves resources.
Keywords: digitalization system; agro-industrial complex; agriculture; business processes; dairy farming